(untitled) (Informatica, 2018)
We present a web application to inform users about different types of viral hepatitises. The core of the application is a questionnaire about past behaviour and risk factors. Based on the answers, it produces a personalised overview of any risky actions that the user might have taken in the past. The site also contains general information about these diseases, which can help users identify them or seek proper precautions in order to avoid them.